2005
DOI: 10.1111/j.1365-3091.2005.00743.x
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of modelled mixing patterns in loess grain‐size distributions: an example from the north‐eastern margin of the Tibetan Plateau, China

Abstract: Genetically meaningful decomposition (unmixing) of sediment grain‐size distributions is accomplished with the end‐member modelling algorithm. Unmixing of the loess grain‐size distributions of a Late Quaternary loess–palaeosol succession from the north‐eastern Tibetan Plateau indicates that the loess is a mixture of three end‐members representing very fine sandy, coarse silty and medium silty loess. The unmixing approach potentially enables the unravelling of sediment fluxes from multiple dust sources, opening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 33 publications
3
41
1
Order By: Relevance
“…Modal grain sizes in this range (ca. 75 µm) are common in loess along the Huangshui and Yellow rivers in China (Prins et al, 2009;Vandenberghe et al, 2006;Vriend and Prins, 2005), the Danube and Tisza rivers in Serbia (Bokhorst et al, 2011), and the Mississippi valley in the USA (Jacobs et al, 2011). Since this fraction is interpreted to originate from proximal sources, the grain size of the available source material, rather than wind energy, plays a more important role in the presence and proportions of this grain size (Vandenberghe, 2013).…”
Section: Genetic Interpretations Of End-members In Loess Grain Sizementioning
confidence: 99%
“…Modal grain sizes in this range (ca. 75 µm) are common in loess along the Huangshui and Yellow rivers in China (Prins et al, 2009;Vandenberghe et al, 2006;Vriend and Prins, 2005), the Danube and Tisza rivers in Serbia (Bokhorst et al, 2011), and the Mississippi valley in the USA (Jacobs et al, 2011). Since this fraction is interpreted to originate from proximal sources, the grain size of the available source material, rather than wind energy, plays a more important role in the presence and proportions of this grain size (Vandenberghe, 2013).…”
Section: Genetic Interpretations Of End-members In Loess Grain Sizementioning
confidence: 99%
“…Vriend and Prins (2005) used the end-member modelling technique to decompose a loesspalaeosol sequence from the northeastern Tibetan Plateau into a series of end members. A mixing experiment with artificial sediment standards similar to their modelled end members indicated that their measurement device (the same Fritsch laser-diffraction particle sizer used in this study to analyse sections X and Z) is sensitive to small variations in mixing coefficients of the sediment populations that make up the artificial mixtures.…”
Section: Discussionmentioning
confidence: 99%
“…Profiles A, B and F with lithologic data. Based on the calibration experiment by Vriend & Prins (2005) it is assumed that the end-member (EM)…”
Section: Subdivision Of the Clay Unitmentioning
confidence: 99%